KEPERLUAN HAFAZAN HADITH DALAM KALANGAN PELAJAR SEKOLAH TAHFIZ: PANDANGAN GURU-GURU AGAMA DI KUALA LUMPUR DAN PUTRAJAYA: The Significance of Hadith Memorization for Tahfiz Students: Perspectives of Islamic Religious Teachers in Kuala Lumpur and Putrajaya - Mohd Saidi, Nadia Farhana; Jamil, Asyraf Isyraqi (Journal of Islamic Educational Research, 2020)
Nowadays, it is undeniable that tahfiz education is increasingly gaining popularity among the society. Various efforts have been made by the authorities to ensure that tahfiz education reaches a certain standard of quality in order to produce more excellent students as our national assets. This study could be seen as an effort to improve the current curriculum of tahfiz students through an analysis of the needs and significance of hadith memorization for tahfiz students. Hence, this study discusses the aspects of hadith memorization from the literature review and a quantitative approach. A survey was conducted on 210 Islamic teachers at 26 tahfiz schools in Kuala Lumpur and Putrajaya. A questionnaire consisting of 6 items of the significance of hadith memorization was developed to get the views of the respondents. The findings of this study showed very positive results, of which five out of six items were rated highly agreeable and could be interpreted as "very essential". The two highest rated items are focusing on the Prophet Muhammad PBUH, which are to appreciate his personality and to encourage the students to love him. The positive results of this study can be applied as a basis and an initial idea for a further study of hadith memorization in the context of tahfiz students. This study, which is focused only on private tahfiz institutions in Kuala Lumpur and Putrajaya, proposes that further studies to be conducted in other locations with an outstanding history and development of tahfiz education such as Terengganu and Kelantan for a more extensive and dynamic result.